PENGARUH MOTIVASI, DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT BENWIN INDONESIA DI KOTA BATAM - Sherlie, Sherlie; Hikmah, Hikmah (Universitas Muhammadiyah Palembang, 2020)
ABSTRACT Purpose - This study airms to determine the effect of motivation, work discipline and compensation on employee performance at PT Benwin Indonesia in Batam City.Design/methodology - The number of samples taken for this study were 103 respondents. The sample collection technique in this study was carried oit by sampling saturation. The data collection technique used in this study was a questionnaire distributed to all employees of PT Benwin Indonesia. The calculation process uses SPSS Software version 25.0. data analysis method in this research uses multiple linear regression analysis.Findings - The results showed that motivation, work discipline and parcial and simultaneous compensation significantly affected employee performance at PT Benwin Indonesia. The value of R square is 0.194 or 19.4%. this shows that motivation, work discipline and compensation influence 19,4% of employee performance while the remaining 80,6% is influenced by other variables outside of this study.Keywords :Compensation, Employee Perfomance, Motivation, Work Discipline.